MULTIFACTORIAL ETIOLOGY OF ATIPICAL HEMOLYTIC UREMIC SYNDROME-CASE REPORT - Skoric, Jasmina; Klacar Uzelac, Marija; Kostic, Ana (Sanamed, 2024)
Introduction: Hemolytic uremic syndromes are characterized by the simultaneous occurrence of hemolytic anemia, microangiopathy, thrombocytopenia, and acute renal insufficiency. In terms of the clinical prodrome, they can be classified as typical, which is more common and occurs in 90% of cases, often preceded by diarrheal syndrome induced by enterohemorrhagic Escherichia coli. Alternatively, there is an atypical and rarer form associated with pneumococcal infection, dysregulation of the alternative complement pathway, and cases involving the use of cyclosporine. Hemolytic anemia is confirmed in laboratory analyses (presence of fragmented red blood cells, decreased hemoglobin, undetectable haptoglobin values, and elevated LDH values), along with thrombocytopenia and an increase in nitrogenous substances (urea and creatinine). Case report: The report details the case of an 18-month-old girl who experienced acute renal insufficiency subsequent to a respiratory infection. Ten days preceding admission, the patient exhibited nasal discharge, and during the seven days leading up to hospitalization, she presented with fever. Furthermore, two days prior to admission, the onset of persistent vomiting and abdominal pain occurred. Suspected of bowel intussusception, the patient underwent a surgical assessment where acute surgical pathology was ruled out. The absence of urination, coupled with heightened urea and creatinine levels, prompted consideration of hemolytic-uremic syndrome, later confirmed as atypical during hospitalization. This was grounded in the clinical presentation, devoid of diarrhea syndrome but marked by nasal discharge over the preceding ten days. The administration of fresh frozen plasma yielded no improvement, and there were decreased values of the C3 complement component, H factor, and reduced ADAMTS13 activity. The lack of verotoxins from enterohemorrhagic Escherichia coli further supported the diagnosis of atypical hemolytic-uremic syndrome. After the first dose of eculizumab, a terminal complement C5 component inhibitor, the girl recovered renal function and established diuresis. Conclusion: The prompt diagnosis of atypical hemolytic-uremic syndrome is challenging due to nonspecific symptoms like nasal discharge, vomiting, fatigue, and abdominal pain. Laboratory analyses, lacking specific criteria, make it difficult to conclusively identify aHUS at the disease’s onset. In Serbia, pneumococcal immunization is recommended as a preventive measure, administered through a conjugated vaccine in three doses starting from the second month of life. Rapid and accurate differentiation between typical and atypical HUS is crucial for effective treatment and prognosis. Typical HUS requires hemodialysis and plasmapheresis, whereas atypical HUS is managed with plasmapheresis, immunosuppressive therapy, and eculizumab. Administering eculizumab heightens the risk of meningococcal infection by inhibiting the C5 complement component. Therefore, it is crucial not to disregard the importance of meningococcal immunization.